Characterization Of Cooperative Control For Multiple Non-Holonomic Wheeled Mobile Robots To Achieve Formation Tracking - Lee, Zhi Xian (2017)

(untitled)
Distributed control for cooperative system is an emerging research eld in control system. This research focuses on characterization of the distributed control algorithm in solving formation tracking for multiple non-holonomic wheeled mobile robots. The existing research work mostly used mathematical approach to proof the convergence of controller but does not investigate how the parameters would aect the controller. Besides, usually only one communication topology is presented in solving formation tracking. Therefore, this research aims to ll in the gap on current research by performing characterization of gain parameters in the distributed controller studied. Besides, several communication topologies are evaluated to understand how the neighbouring agents connected will impact the performance. A multi-agent system that consists of four wheeled mobile robots are investigated in this research using simulation approach. LabVIEWTM is used to simulate the multi- agent formation control. This research managed to perform the characterization of gain parameters and evaluate dierent communication topologies. The characterization would complement the existing Lyapunov analysis thereby improving the research in cooperative formation control of wheeled mobile robot. This has helped to understand the how the distributed controller studied and used to tune the con- troller to solve the formation tracking. The formation tracking control is partially achieved and can be further improved by making the parameters adaptive to achieve state consensus.